Braces versus casts for post-operational immobilization of ankle fractures: A meta-analysis - Li, Bin; Xie, Jianying; Zhang, Zhengmao; Liu, Quanyong; Xu, Jialie; Yang, Chenxi (Frontiers in Surgery, 2023)
Background and aims Both casts and braces can be used for post-operational immobilization of ankle fractures. This meta-analysis aimed to assess the complications and functional effects of the two types of immobilization. Material and methods PubMed, Embase, Cochrane, and CNKI was searched for randomized controlled trials (published between Jan 1, 1950, and March 2022). Relative risk (RR) or standard mean difference (SMD) with a 95% confidence interval (CI) was used to present the outcomes. The pooled data were assessed by using the fixed-effects model or random-effects model. Results A total of 5 randomized controlled studies involving 930 subjects were included according to our inclusion criteria. On the ankle score at 6w,12w and 52w, there was no statistically significant difference between the two groups. In terms of 6w, the brace group showed better ankle dorsiflexion (MD = 6.78, 95% CI 0.56–13.00, p = 0.03) and plantar flexion (MD = 6.58, 95% CI 1.60–11.55, p = 0.01) than the cast group. The wound complications (RR = 3.49, 95% CI 1.32 to 9.24, p = 0.01) and total complications (RR = 3.54, 95% CI 1.92 to 6.50, p < 0.0001) in the brace group were three times more than that in the cast group. There was no statistically significant difference between the two groups in the non-wound complications. There was no statistically significant difference between the two groups in the time of going back to work, swelling of the ankle, and atrophy of the calf muscle. Conclusion The short-term and long-term functional outcomes after postoperative treatment of adult ankle fractures with braces are similar to those with casts. The usage of braces may cause three times more wound complications than that of casts.